A var2 leaf variegation suppressor locus, SUPPRESSOR OF VARIEGATION3, encodes a putative chloroplast translation elongation factor that is important for chloroplast development in the cold - Yu Fei; Rodermel Steve R; Liu Xiayan (BMC Plant Biology, 2010)
Abstract Background The Arabidopsis var2 mutant displays a unique green and white/yellow leaf variegation phenotype and lacks VAR2, a chloroplast FtsH metalloprotease. We are characterizing second-site var2 genetic suppressors as means to better understand VAR2 function and to study the regulation of chloroplast biogenesis. Results In this report, we show that the suppression of var2 variegation in suppressor line TAG-11 is due to the disruption of the SUPPRESSOR OF VARIEGATION3 (SVR3) gene, encoding a putative TypA-like translation elongation factor. SVR3 is targeted to the chloroplast and svr3 single mutants have uniformly pale green leaves at 22°C. Consistent with this phenotype, most chloroplast proteins and rRNA species in svr3 have close to normal accumulation profiles, with the notable exception of the Photosystem II reaction center D1 protein, which is present at greatly reduced levels. When svr3 is challenged with chilling temperature (8°C), it develops a pronounced chlorosis that is accompanied by abnormal chloroplast rRNA processing and chloroplast protein accumulation. Double mutant analysis indicates a possible synergistic interaction between svr3 and svr7, which is defective in a chloroplast pentatricopeptide repeat (PPR) protein. Conclusions Our findings, on one hand, reinforce the strong genetic link between VAR2 and chloroplast translation, and on the other hand, point to a critical role of SVR3, and possibly some aspects of chloroplast translation, in the response of plants to chilling stress.